Multidisciplinary Therapy Managed Recurrent Glioblastoma in a BRAF-V600E Mutant Pregnant Female: A Case Report and Review of the Literature - Qin, Chaoying; Long, Wenyong; Zhang, Chi; Xie, Yuanyang; Wu, Changwu; Li, Yang; Xiao, Qun; Ji, Nan; Liu, Qing (Frontiers in Oncology, 2020)
Abstract Background: Glioblastoma (GBM) is the most malignant intracranial tumor in adults. However, the overall management of GBM in pregnancy is rarely reported. How to balance the therapeutic benefits to the mother and risks to the fetus remains hugely challenging for clinicians. The application of specific targeting therapy combined with conventional treatment sheds light on a longer lifetime for the patients suffering from GBM. Case Presentation: We present a pregnant female diagnosed with GBM. Surgical resection was initially performed without adjuvant therapy, and the tumor recurred de novo two months later. A secondary craniotomy and cesarean section were performed simultaneously, both the patient and infant were survived. She was subsequently treated with traditional chemo-radiotherapy. No other identified genetic alterations indicating an optimistic prognosis were detected except for BRAF V600E mutation was detected. Thus the BRAF inhibitor was placed on her with achieving a good clinical outcome of more than two-year survival without recurrence. Conclusion: Personalized multidisciplinary therapy should be considered when GBMs occur in pregnancy. Response to the therapy in this presenting case suggests that BRAF V600E mutation is a favorable biomarker for GBM. The mortality of GBM might be reduced through genetic testing and targeted treatment. However, more studies must be conducted to confirm our observation.